Practical Issues in Tax Proceedings in the Czech Republic - Čejková, Tereza; Nevečeřalová, Nikol (Public Governance, Administration and Finances Law Review, 2018)
This contribution deals with practical problems of entities obligated to a tax and of tax administrators. If the collection of taxes and fees is essential to finance the running of the state and its authorities and organizational units, it is necessary to make this process as simple as possible, the least demanding and demotivating. In this paper, the authors will examine in terms of legality and real necessity, and then there may be other legislation ways proposed.